2018
DOI: 10.1183/23120541.00119-2017
|View full text |Cite
|
Sign up to set email alerts
|

Single-inhaler triple therapy in symptomatic COPD patients: FULFIL subgroup analyses

Abstract: Triple inhaled corticosteroid (ICS)/long-acting muscarinic antagonist (LAMA)/long-acting β2-agonist (LABA) therapy is recommended for symptomatic patients with chronic obstructive pulmonary disease (COPD) and at risk of exacerbations. However, the benefits versus side-effects of triple inhaled therapy for COPD, based on distinct patient clinical profiles, are unclear.FULFIL, a phase III, randomised, double-blind study, compared 24 weeks of once-daily fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In addition, the NNT for 1 year to prevent one additional moderate/severe COPD exacerbation in BGF MDI versus GFF MDI was similar in both subgroups (no prior history: 3; prior history: 2). While other triple therapy studies included patients with differing exacerbation risks (eg 1 versus 2 or more), with the exception of the FULFIL study, 7 , 12 none included patients with no prior exacerbations. 4 , 5 , 8 , 9 The 24-week FULFIL study was conducted in symptomatic patients with moderate-to-very severe COPD and showed that annual moderate/severe exacerbation rates were improved by triple therapy versus ICS/LABA regardless of a history of exacerbations (0/1 moderate exacerbations, ≥2 moderate exacerbations, or ≥1 severe exacerbation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the NNT for 1 year to prevent one additional moderate/severe COPD exacerbation in BGF MDI versus GFF MDI was similar in both subgroups (no prior history: 3; prior history: 2). While other triple therapy studies included patients with differing exacerbation risks (eg 1 versus 2 or more), with the exception of the FULFIL study, 7 , 12 none included patients with no prior exacerbations. 4 , 5 , 8 , 9 The 24-week FULFIL study was conducted in symptomatic patients with moderate-to-very severe COPD and showed that annual moderate/severe exacerbation rates were improved by triple therapy versus ICS/LABA regardless of a history of exacerbations (0/1 moderate exacerbations, ≥2 moderate exacerbations, or ≥1 severe exacerbation).…”
Section: Discussionmentioning
confidence: 99%
“…4,5,8,9 The 24-week FULFIL study was conducted in symptomatic patients with moderate-to-very severe COPD and showed that annual moderate/severe exacerbation rates were improved by triple therapy versus ICS/LABA regardless of a history of exacerbations (0/1 moderate exacerbations, ≥2 moderate exacerbations, or ≥1 severe exacerbation). 12 Approximately one third of patients in the FULFIL study had no documented history of moderate/severe exacerbations in the previous year. 7 ICS-containing regimens are not generally recommended for symptomatic patients who do not report exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…A full-text analysis led to the removal of 90, leaving 15 records (seven abstracts/posters) belonging to six studies for inclusion ( Fig. 1) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Detailed reasons for exclusion are outlined in Additional file 1: Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…However, the converse was also found in comparisons with LAMA/LABA (TRIBUTE) and LABA/ ICS (IMPACT [21]) where triple therapy demonstrated a higher reduction in the rate of moderate and severe exacerbations in patients who experienced fewer historical exacerbations compared to those with a higher frequency of historical exacerbations. A post-hoc analysis of data from the FULFIL study showed that, compared with LABA/ICS, triple therapy resulted in a significantly higher reduction in moderate and severe exacerbation rates in patients who had experienced ≥1 severe exacerbation, and 0/1 moderate exacerbations; patients who experienced ≥2 moderate exacerbations also experienced a rate reduction but the difference was not statistically significant [20]. There were no data relating to prior exacerbation frequency subgroups in the KRONOS study.…”
Section: Prior Exacerbation Frequency Subgroupmentioning
confidence: 97%
“…Singh et al, 2016 (TRILOGY) 67 Vestbo et al, 2017 (TRINITY) 70 Lipson et al, 2017 (FULFIL) 65 Papi et al, 2018 (TRIBUTE) 71 Halpin et al, 2018 (FULFIL) 86 Patients with eosinophils ≥300 cells/mL and a history of ≥ 1 exacerbation in previous year…”
Section: Ics Withdrawalmentioning
confidence: 99%